Masterpiece of epigenetic engineering - how Toxoplasma gondii reprogrammes host brains to change fear to sexual attraction - Flegr, Jaroslav; Markoš, Anton (Molecular ecology, 2014)
The protozoan parasite Toxoplasma gondii is known to induce specific behavioural changes in its intermediate hosts, including humans, that are believed to increase the chance of its successful transmission to the definitive host, the cat. The most conspicuous change is the so-called fatal attraction phenomenon, the switch from the mice's and rats' natural fear of the smell of cats toward an attraction to this smell. The mechanism of this manipulation activity is unknown; however, many indices suggest that changes in the concentrations of dopamine and testosterone are involved. In this issue of Molecular Ecology, Hari Dass & Vyas (2014) present results of a study showing that, by hypomethylation of certain regulatory elements of key gene, Toxoplasma is able to reprogramme the brain's genetic machinery in such a way that cat odour activates and changes the wiring of the medial amygdala circuits responsible for sexual behaviour. This study delivers the first clear evidence of a parasite's ability to use sophisticated epigenetic engineering techniques for the manipulation of the phenotype of its infected host.
Keywords: Fear; strach; evolutionary parasitology; chování zvířat; Epigenesis, Genetic; gene expression; manipulation hypothesis; toxoplasmosis; Host-Parasite Interactions; methylation; zvířata; epigenetics; amygdala; epigeneze genetická; Male; Amygdala; testosterone; toxoplazmóza zvířat; Animals; Toxoplasmosis, Animal; mužské pohlaví; interakce hostitele a parazita; Behavior, Animal